Identification of Peptides Derived from the Human Antimicrobial Peptide LL-37 Active against Biofilms Formed by Pseudomonas aeruginosa Using a Library of Truncated Fragments - Nagant, C. (American Society for Microbiology, 2012)
Persistent Pseudomonas aeruginosa infections are a major cause of morbidity and mortality in cystic fibrosis (CF) patients and are linked to the formation of a biofilm. The development of new biofilm inhibition strategies is thus a major challenge. LL-37 is the only human antimicrobial peptide derived from cathelicidin. The effects on the P. aeruginosa PAO1 strain of synthetic truncated fragments of this peptide were compared with the effects of the original peptide. Fragments of LL-37 composed of 19 residues (LL-19, LL13-31, and LL7-25) inhibited biofilm formation. The strongest antibiofilm activity was observed with the peptides LL7-37 and LL-31, which decreased the percentage of biomass formation at a very low concentration. Some peptides were also active on the bacteria within an established biofilm. LL7-31, LL-31, and LL7-37 increased the uptake of propidium iodide (PI) by sessile bacteria. The peptide LL7-37 decreased the height of the biofilm and partly disrupted it. The peptides active within the biofilm had an infrared spectrum compatible with an α-helix. LL-37, but not the peptides LL7-31 and LL7-37, showed cellular toxicity by permeabilizing the eukaryotic plasma membrane (uptake of ethidium bromide and release of lactate dehydrogenase [LDH]). None of the tested peptides affected mitochondrial activity in eukaryotic cells. In conclusion, a 25-amino-acid peptide (LL7-31) displayed both strong antimicrobial and antibiofilm activities. The peptide was even active on cells within a preformed biofilm and had reduced toxicity toward eukaryotic cells. Our results also suggest the contribution of secondary structures (α-helix) to the activity of the peptides on biofilms.